The Role of Biomechanical Forces in the Formation and Treatment of Pathological Scars - Cao G; Ye M; Wang H; Liu Y; Li M (Dove Medical Press, 2024)
Guangtong Cao,1 Mingmin Ye,2 Haiyan Wang,3 Yi Liu,1,* Mengzhi Li4,* 1Department of Burns and Plastic Surgery & Wound Repair Surgery, Second Hospital of Lanzhou University, Lanzhou, Gansu, 730030 People's Republic of China; 2Department of Plastic Surgery, Gansu Provincial Hospital, Lanzhou, Gansu, People's Republic of China; 3Department of Ultrasound Medicine, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 4Department of Hand, Foot, and Microsurgical Reconstruction, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Yi Liu; Mengzhi Li, Email liuyi196402@163.com; sweetlife00@163.comAbstract: Pathological scars, including hypertrophic scar and keloid are the result of excessive tissue repair and are influenced by biomechanical forces like tension, mechanical pressure, and stiffness. These forces significantly impact scar development and progression, affecting wound healing, collagen deposition, and tissue remodeling. Understanding how these mechanical stimuli contribute to scar development is essential for devising effective therapeutic interventions. Clinically, reducing wound tension and applying mechanical pressure are key strategies for managing pathological scars. Techniques like super-tension-reduction suturing, stress-shielding polymers, and force-modulating tissue bridges (FMTB) have been shown to effectively alleviate tension and reduce scar proliferation. Additionally, Pressure Garment Therapy (PGT) is widely used to treat hypertrophic scars by reducing tissue stiffness, limiting collagen buildup, and promoting collagen realignment. Despite challenges such as discomfort and uneven pressure application, ongoing research focuses on enhancing these therapies through mechanosensitive technologies to improve both efficacy and patient comfort. This review highlights the role of biomechanical forces in scar formation and discusses therapeutic approaches that target these forces to improve clinical outcomes.Keywords: pathological scars, biomechanical forces, hypertrophic scar, keloid, tissue remodeling